Defects in Saccharomyces cerevisiae protein phosphatase type I activate the spindle/kinetochore checkpoint - Bloecher, Andrew (Cold Spring Harbor Laboratory Press, 1999)
A conditional allele of type 1 protein phosphatase (glc7-129) in Saccharomyces cerevisiae causes first cycle arrest in G(2)/M, characterized by cells with a short spindle and high H1 kinase activity. Point-of-execution experiments indicate Glc7p function is required in G(2)/M just before anaphase for the completion of mitosis. Loss of the spindle/kinetochore checkpoint in glc7-129 cells abolishes the G(2)/M cell cycle arrest with a concomitant increase in chromosome loss and reduced viability. These results support a role for Glc7p in regulating kinetochore attachment to the spindle, an event monitored by the spindle/kinetochore checkpoint.